A novel three-dimensional spherical CuBi2O4 consisting of nanocolumn arrays with persulfate and peroxymonosulfate activation functionalities for 1H-benzotriazole removal - Oh, Wen-Da (2015)
A novel CuBi2O4 consisting of self-assembled spherical nanocolumn arrays (CuB-H) was synthesized via a facile hydrothermal method. It was further modified by controlling the Cu:Bi ratio during synthesis to become an efficient bi-functional catalyst (CuB-2.5) activated persulfate (PS) and peroxymonosulfate (PMS) for 1H-benzotriazole (BTZ) removal. Characterization of CuB-2.5 using XRD, FESEM, FTIR, BET and XPS revealed that it was morphologically similar to CuB-H and the molecular formula, as determined from the XRD results, was Cu1.2Bi1.6O3.6 with 2.4% w/w of CuO. The CuB-2.5 catalyst exhibited superior performance for BTZ removal via PS and PMS activations over the Cu2+ (aq.), CuO, CuBi2O4 (CuB-M, microsphere) and CuB-H. The performance of CuB-2.5 was investigated at different initial PS/PMS dosages, initial catalyst loadings and initial BTZ concentrations. Interestingly, it was found that the inter- and intra-molecular hydrogen bondings play prominent roles in the BTZ removal mechanism in both the PS and PMS systems. Meanwhile, it is relatively easy to activate PMS, leading to a faster BTZ removal rate over the PS system. The intermediate products of BTZ degradation produced from the PS and PMS systems were similar, indicating a similar degradation pathway. The catalyst could still retain its morphology and can be reused multiple times. Keywords: Persulfate activation; Peroxymonosulfate activation; Sulfate radical; Hydroxyl radical; Benzotriazole.